Synthesis and Structure–Activity Relationships of Aristoyagonine Derivatives as Brd4 Bromodomain Inhibitors with X-ray Co-Crystal Research - Minjin Yoo; Tae Hyun Park; Miyoun Yoo; Yeongrin Kim; Joo-Youn Lee; Kyu Myung Lee; Seong Eon Ryu; Byung Il Lee; Kwan-Young Jung; Chi Hoon Park (Molecules, 2021)
Epigenetic regulation is known to play a key role in progression of anti-cancer therapeutics. Lysine acetylation is an important mechanism in controlling gene expression. There has been increasing interest in bromodomain owing to its ability to modulate transcription of various genes as an epigenetic ‘reader.’ Herein, we report the design, synthesis, and X-ray studies of novel aristoyagonine (benzo[6,7]oxepino[4,3,2-cd]isoindol-2(1H)-one) derivatives and investigate their inhibitory effect against Brd4 bromodomain. Five compounds 8ab, 8bc, 8bd, 8be, and 8bf have been discovered with high binding affinity over the Brd4 protein. Co-crystal structures of these five inhibitors with human Brd4 bromodomain demonstrated that it has a key binding mode occupying the hydrophobic pocket, which is known to be the acetylated lysine binding site. These novel Brd4 bromodomain inhibitors demonstrated impressive inhibitory activity and mode of action for the treatment of cancer diseases.